THE POWER OF STATE, THE RIGHT OF PARENTS, THE RIGHT OF THE CHILD – THE RIGHT TO EDUCATION AS THE RIGHT TO POSSESS CONTROL - Butrymowicz, Magdalena (Review of European and Comparative Law, 2017)
Why does the state have power in the area of education over parents’ wishes? The first reason has already been explained above: these are financial and economic aspects. The second reason is of historical nature. The state has controlled education in general historically. When in the 19th century the idea of public schools was created, the state sponsored such schools. Private schools were in a good condition, since they had their own sponsors or proceeds from pupils’ tuitions. When they lost their self-sustainability, they had to request the state for some support. And, as mentioned above, the state had its interest in controlling the educational system, because it wanted to influence the upbringing process of its citizens and create an ideology, which would help to achieve the government’s goal.